Mediating Effect of External Factors to the Relationship Between Leadership Styles and Organizational Performance - Ali Alshehhi, Hamad; Jano, Zanariah; Kudus, Norliah (International Journal of Sustainable Construction Engineering and Technology, 2023)
Inappropriate leadership style harms employees and the organization's overall performance. Lack of leadership likely causes unethical practises, high turnover, and employee disengagement. Many of the organization's problems are attributed to incompetent or mismatched administrators. They may use an inappropriate leadership style with project subordinates. There is lack of studies on leadership styles and organisational performance, especially in oil and gas organisations. Hence, this research examines the relationship leadership styles and organisational performance of ADNOC company. This study involved questionnaire survey for data collection and analysis of 398 questionnaire forms was carried out through structural equation modelling. The study established a mediation model where the external factors act as mediator to the relationship. Based on the assessment on the model, it was found that Charismatic and Democratic leadership styles have a significant impact on organisational performance while Transformational and Transactional do not have significant effect on the organization performance. Also, external environment is proven as mediator of Charismatic and Democratic leadership styles. Overall, the developed model can assist for adopting the leadership style in achieving the successful organizational performance of ADNOC Company.